Tamira - Asrari, Behrooz (Iran : Setak Film Sanandaj, 2008)
Tabouras are interesting, elegant and beautiful instruments. They come in various shapes, forms and colors. This short film is animated by such an instrument. Behrooz Asrari travels to Gahvareh, an Iranian village, to meet Mr. Asadolah who makes Tabouras. With Mr. Asadolah’s help and willingness, the director manages to record the metamorphosis of a simple piece of wood into a beautiful musical instrument.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films